PENGARUH KEPEMIMPINAN TERHADAP KOMITMEN ORGANISASI DIMEDIASI OLEH KOMUNIKASI ORGANISASI PADA PT. BANK ANTARDAERAH - Redi Setiawan, I Gede; Sudharma, I Nyoman (E-Jurnal Manajemen; Vol 4 No 12 (2015), 2015)
To keep organization commitment hence leadership role and organization communication very needed in order to organizational goal can be reached. If organization commitment has been obtained then it will get loyal employee and they will able to work by well for organization purpose. To analysis the effect leadership, and organization communcation toward organization commitment and to find out the organization communication role in mediate leadership with organiztion commitment at PT. Bank Antardaerah as purpose of this study. Path analysis was data analysis method was applied to analysis the pattern of causality relationship between variables. Research questioner was obtained to collect data. All employee of PT. Bank Antardaerah equal to 51 people as population at same time as sample in this study. The result of analysis shows direct effect is positive and significant toward organization commitment, the same effect have by the leadership toward organization communication. Thus also organization communication variable shows same effect toward organization. Organization communication able to mediate leadership toward organization commitment
Keywords: leadership, organization communication, organization commitment